Smolnytska O. The Electra Complex in the Novel Mind of the 20th–21st Centuries: according to Nila Zborovska’s Method - O. Smolnytska (Philological Treatises, 2020)
Narrative prose (fiction novel) of the second half of the 20th – the second decade of the 21st centuries is a difficult writing. In particular, this is either a mythopoetical material, or a conscious opposition or confrontation to the myth. However, mythological patterns, also as national archetypes and symbols, are still explicitly or implicitly presented in such texts. The article offers a more detailed overview of the Electra complex on the example of the chosen romanticism of the period, with an emphasizing on the feminine character. According to the method of the Ukrainian psychoanalyst Nila Zborovska (1962–2011), the role of maternal and paternal codes in literature of different periods (since the 19th century) is compared. A mythological model (paternal or maternal) in different types of cultures and the possibility of its reflection in different literatures have been worked out. The paternal and maternal images are regarded as ambivalent deities, the strong Animus and Anima are analyzed in the aspect of dictates. The principles of the image of feminine characters in classical (mostly Victorian) and non-classical (modern) novels are compared. Attention is drawn to the clinical picture of the heroines of modern works. The works of Ch. Dickens, F. Dostoevsky, S. Zweig, J. O'Neill, J. Steinbeck, S. Plath, B. Kaufman, E. Jelinek, D. Levy, etc. are taken into account. The national aspect in the mother complex is investigated. The transfer of imperial and postcolonial discourse on behavioral models of these feminine characters is analyzed. Attention is drawn to the clinical picture of the heroines of the modern works. The differences in the images of heroines in different periods are analyzed, the common feature as their resistance to the mechanism of subordination is found. The modern heroine has the features of homo technicus or homo technologicus, her described protest, on the one hand, is allusional (it recalls the behavior of the characters of S. Plat or E. Jelinek), on the other hand, it is manfully artificial affected. Research methods: comparative (of philology and mythology), archetypal (Jungian), Freudian, symbological, gender studies, also attention is drawn to the historical context.